Fruggies for All: Evaluation of an integrated nutrition-sensitive project targeted to increase fruit and vegetable consumption in urban Vietnam and Nigeria - Pastori, Giulia (Wageningen University & Research, 2023)
Fruits and vegetables (FV) are important components of healthy diets. However, global consumption is low, especially in low- and middle-income counties. Several are the determinants of FV consumption that can be addressed to increase consumption. Nutritionsensitive interventions that target the consumer and supply side of the food system have the potential to promote FV consumption in low-income populations. Using the examples of Vietnam and Nigeria, with a focus on urban contexts, we aimed to evaluate the integrated nutrition-sensitive FVN project that aimed to increase FV consumption of low-income adults in urban and peri-urban Hanoi and Ibadan and to develop an indicator to monitor FV intake. This thesis aims to characterize the dietary patterns of consumers living in urban and periurban Hanoi, Vietnam and Ibadan, Nigeria, and to evaluate the FVN project through the monitoring of FV intakes during the implementation of the interventions and a final evaluation of FV intakes. Additionally, it aims to validate a simple score to assess FV consumption at the population level.